Pengaruh Brand Ambassador, Viral Marketing, Dan Brand Trust Terhadap Keputusan Pembelian Sepatu Mills Pada Club Futsal Universitas Islam Malang - Hammam, An’im; Hidayati, Nur; Suharto, M. Khoirul Anwarudin Broto (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of Brand Ambassador, Viral Marketing, and Brand Trust on the purchasing decisions of Mills shoes among the Futsal Club at Universitas Islam Malang. The research employed a quantitative approach with an explanatory research design. Data were collected through surveys using questionnaires distributed to 50 members of the Universitas Islam Malang Futsal Club who had previously purchased Mills shoes. Data analysis was conducted using statistical tests to measure the simultaneous and partial effects of the independent variables on the dependent variable.The results of the study indicate that Brand Ambassador, Viral Marketing, and Brand Trust simultaneously have a significant influence on the purchasing decisions of Mills shoes. Partially, Brand Ambassador has a positive and significant effect on purchasing decisions. Conversely, Viral Marketing and Brand Trust do not show significant partial effects on purchasing decisions. Based on these findings, it is recommended that the company be more selective in choosing Brand Ambassadors with high appeal and credibility that are relevant to the futsal community. Viral Marketing strategies should be evaluated to create more engaging and relevant content, while efforts to build Brand Trust can focus on improving product quality, customer service, and brand transparency. Keywords: Brand Ambassador, Viral Marketing, Brand Trust, Purchasing Decisions, Mills Shoes.